Educate for social commitment, ideal or nerve configurator of the educational structure? (Journal of Parents and Teachers, 2014)
In this article we are invited to review the operation of Education for the solidarity and participation that this should have in schools. It gives us a series of guidelines such as the importance of discovering and exploring the faces of poverty.
Keywords: reality; integrate; share; coexist; ONG